The Kosovo War In The British Parliament Talks In 1999 - Simon Lufi; Marsel Nilaj (European Scientific Journal, ESJ, 2016)
The Kosovo War in the 1990s was one among a series of wars in the former Yugoslav federation. It was the final war that ended the dissolution which had started with Slovenia from1990 to 1991, Croatia and Bosnia - Herzegovina from 1992 to 1995 and the Kosovo War from 1998 to 1999. However, the Kosovo war happened during a different situation and period. It was at a time and in a position to cause the domino effect in the Balkans and an outbreak of wars in a large part of the Balkans. This fight could include Albania and Macedonia as nations with an ethnic Albanian population. It could also have a religious or cultural impact that threatened to involve other states such as Bosnia and Turkey on the one hand and Greece on the other. The interest of major countries in Europe, as well as the world, was focused on this war. A country among them was the UK. As one of the founding states of the European Union, United Nations, and NATO, the UK was quite involved in this war. The UK and the US were two countries that became the political and military leadership in this struggle since its beginning, while reaching a peak in 1999. This situation involved talks in the British Parliament in the UK, especially the House of Lords where the decision-making aspect of parliamentary politics is achieved. The war was also a major concern for the parliament. On the one hand, it was important to resolve the situation in Kosovo without worsening it with other massacres. On the other hand, this situation required caution in dealing with the Serbian people. The destiny of Kosovo refugees was important to them. However, the future of the Serbian people in Kosovo had to be guaranteed. The most important thing was to obtain full autonomy for Kosovo, but also to achieve a bilateral cooperation from both countries. The House of Lords and the interest of some lords in this war made the British policy, as a whole, a lot more responsible for accomplishing what it had started since diplomacy regarding weapons and the military intervention used to manage the situation of refugees in Kosovo had a huge impact in Europe. The British parliamentary sessions were very crucial in leading to an international level this whole historical phase for Kosovo.